Fighting in women’s clothes The pictorial evidence of Walpurgis in Ms. I.33 - Julia Gräf (Acta Periodica Duellatorum)
Ms. I.33 is not only the oldest of the known fencing treatises in European context, it is also the only one showing a woman fighting equally with contemporary men. The author presents her research about the garments this female fencer wears, including her shirt, dress and overdress, hairstyle and footwear. Special consideration is given to the questions whether Walpurgis wears a belt, the length and hem circumference of her garments as well as the methods of draping them in the way depicted. The results of the analysis are compared with contemporary pictorial and archaeological sources of the early 14th century. Some personal insights gathered by the author while fighting in this kind of clothes shed light on the possibilities of moving without being disturbed by them. The clothes and hairstyle worn by Walpurgis, give clues about her social status and thus help to understand the context and dating of the whole manuscript.